(untitled) (Kerala Journal of Psychiatry, 2023)
Background: COVID-19 resulted in uncertainties and new normal, which had an impact on nursing education too. Therefore, the study aimed to assess the resilience and to explore the experiences of nursing students during the pandemic. Methods: The study adopted a mixed method design. In the quantitative phase, resilience was assessed using Connor-Davidson Resilience scale among 477 nursing students. The data was collected through google forms. This was followed by qualitative phase in which experiences and resilience was explored by conducting eleven In-depth Interviews and five Focus Group Discussions. The resilience was dichotomised into good and poor resilience based on the median score. Latent content analysis was adopted for qualitative analysis. Results: The mean age was 22.15 (SD 4.42). Majority of the study participants were studying were studying for BSc Nursing 297 (62.3%) and 95(19.9%) were studying for three-year diploma nursing course and 37 (7.8%) of students studying for post-graduation in nursing. The mean resilience score was 71.20 (SD 13.74), 95% CI (69.97- 72.44). Domicile and year of study showed significant association with resilience. Four major themes emerged were psychological torment, Experience related to Covid 19, Experience related to teaching learning activity and Resilience. Conclusion: The present study revealed that the mean resilience score of nursing students was high. Educational strategies have to be developed focusing on promotion of resilience among nursing students so that they can render quality nursing care even during pandemic.